Analysis of shoreline changes along the coastal area of Biak Island (Biak Numfor Regency, Indonesia) using multitemporal Landsat images - Basa T Rumahorbo; Maklon Warpur; Baigo Hamuna; Rosye H.R. Tanjung (Brawijaya University, 2022)
Monitoring shoreline changes is important in detecting abrasion and accretion in coastal areas. This study aimed to determine the level of shoreline change caused by abrasion and accretion and estimate the change rate. The study area covers coastal areas in ten Districts in Biak Numfor Regency (only on Biak Island). Six Landsat image datasets (1997, 2002, 2007, 2013, 2018, and 2022) were used to determine the coastline. Shoreline changes were analysed using DSAS software. The results of digitising the shoreline show a change in the length of the shoreline during the six data periods. Based on NSM and EPR for the last ten years (2013-2022), the average shoreline changes due to abrasion range from -6.65 to -13.16 m with an abrasion rate of -0.76 to -1.50 m/year. Meanwhile, the average shoreline changes due to accretion ranged from 4.64 to 8.45 m with an accretion rate of 0.53 m/year to 0.96 m/year. Changes in shoreline based on the rate of abrasion and accretion vary greatly in each district along the coastal area of Biak Numfor Regency, depending on the EPR value of each transect. Spatially, high abrasion and very high abrasion are widely distributed in Oridek, Biak Utara, Swandiwe, and Warsa Districts. Medium and high accretion were found in Yawosi, Bindifuar, and Oridek Districts. Because there has been a change in the coastline due to abrasion, planning efforts to mitigate coastal areas are very necessary.